Prolonged cholestatic jaundice with very high bilirubin level due to hepatitis e infection - Nandan, Devki; Kumar, Manish; Dewan, Vivek; Sahoo, Chinmaya (International Journal of Basic and Applied Sciences, 2014)
A 12 year old male child presented with jaundice, generalized itching and disturbed sleep of one and half months duration. Extremely high Serum bilirubin levels (total 38.3 mg/dl, direct 27mg/dl, and indirect 11mg/dl) with normal liver enzymes were documented, which gradually resolved over next two months on supportive management. Hepatitis E infection was diagnosed based on presence of positive Anti hepatitis E IgM antibodies. Underlying associated hepato-biliary diseases were ruled out on a detailed work-up of the case. This case is a unique example of prolonged cholestatic jaundice with extremely high levels of bilirubin with normal liver enzymes in a case of hepatitis E, which has not been reported previously in pediatric age group. Keywords: high bilirubin, hepatitis E, Cholestatic jaundice, normal liver enzyme, prolonged jaundice.